Comparison of the Effect of Prefabricated Foot Orthoses on Pain and Quality of Life in Women With Plantar Fasciiti - Maryam Sharifian; Alireza Taheri; Mohammad Taghi Karimi (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective The purpose of the present study was to investigate the effect of soft and semi-rigid prefabricated insoles on the improvement of pain and quality of life in women with plantar fasciitis. Materials & Methods This study was a randomized clinical trial. A society with 30 women diagnosed with plantar fasciitis by physical and rehabilitation physicians, orthopedic practitioners, and other rehabilitation colleagues and referred to an orthopedic clinic of Isfahan University of Medical Sciences . Absolute recognition of plantar fasciitis was performed by the researcher using Windlass mechanism test. In this study, prefabricated soft insoles made from ethyl vinyl acetate with low-density and semi-hardened insoles of ethyl vinyl acetate with high-density were used. The insoles were full-length with an internal longitudinal arch proportional to the size of the feet of each patient. The intervention was randomly divided into two treatment groups. The patients (n=30) were divided into two groups of 15, which consisted of the test and measurement steps. The first group was without intervention, soft insoles and the semi-hardened insoles. The second group was with the stage without intervention, the soft insoles and semi-hardened insoles. Before intervention, the Foot and Ankle score and quality of life questionnaire (SF-36) was completed and then orthoses intervention was performed in two stages. One questionnaire completed after two weeks using orthosis and another six weeks after using orthosis. Normal distribution of data was calculated using Shapiro Wilk test, and for the final analysis, tests of repeated measures ANOVA were used. Statistical calculations were performed using SPSS 20 software and P<0.05 was considered significant. Results The results demonstrated that the difference between the mean quality of life of patients in two stages of without insoles and with soft insoles was significantly higher in comparison to the without insoles stage (P<0.05). This result is same as when without insole stage is compared with semi-rigid insole and mean difference showed that this figure was significantly higher in comparison with the without insoles stage (P<0.05). The mean quality of life is higher in the semi-hard insoles in comparison to soft insole stage and the difference between these two stages is not significant (P˃0.05). The mean of foot and ankle pain in was significantly more inpatient without insole condition in comparison to patient with a soft insole (P<0.05). The mean foot and ankle pain in without insole condition is significantly more than the time when the patient has a semi-rigid insole (P<0.05). While the comparison of the pain score with soft insoles and semi-rigid insoles indicates that the pain level of the foot and ankle is significantly higher with the semi-rigid insoles. Conclusion Based on the present findings, it can be concluded that orthosis intervention, regardless of its gender, has no significant improvement in the quality of life in patients with plantar fasciitis. Furthermore, soft insole reduces the pain of the ankle and foot in these patients.